Comprehensive Physiology 2014
DOI: 10.1002/cphy.c140001
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Endocytic Pathways in Liver Function and Disease

Abstract: Hepatocellular endocytosis is a highly dynamic process responsible for the internalization of a variety of different receptor ligand complexes, trophic factors, lipids, and, unfortunately, many different pathogens. The uptake of these external agents has profound effects on seminal cellular processes including signaling cascades, migration, growth, and proliferation. The hepatocyte, like other well-polarized epithelial cells, posses a host of different endocytic mechanisms and entry routes to ensure the select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 168 publications
(205 reference statements)
0
14
0
Order By: Relevance
“…With the help of the spliceosome, endocytosis acted as one of main activators for finding a series of successive waves of maternal pioneer signal regulators [61]. The misregulation of endocytosis could result in HCC [62].…”
Section: Discussionmentioning
confidence: 99%
“…With the help of the spliceosome, endocytosis acted as one of main activators for finding a series of successive waves of maternal pioneer signal regulators [61]. The misregulation of endocytosis could result in HCC [62].…”
Section: Discussionmentioning
confidence: 99%
“…CME plays important roles in hepatocytes, which uptake various materials physiologically [17] , and it is thought that hepatitis viruses utilize this system. A previous report showed that silibinin attenuated HCV infection via the inhibition of CME, and this study showed it also inhibits HBV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Several other lines of evidence support the notion that CME is the major route of entry for HBV in vivo ( Figure 2 ). Indeed, CME has been shown to play a number of important roles in hepatocytes, in iron homeostasis, hepatic steatosis, and virus-induced liver infections [ 83 ]. In addition to acting as the receptor for HBV, NTCP has a physiological function in the uptake of bile salts and is recycled to the plasma membrane via CME [ 84 ].…”
Section: Mechanisms Of Hbv Entry Into Cellsmentioning
confidence: 99%